Placeholder factors in ribosome biogenesis: please, pave my way - Francisco J. Espinar-Marchena; Reyes Babiano; Jesús de la Cruz (Microbial Cell, 2017)
The synthesis of cytoplasmic eukaryotic ribosomes is an extraordinarily energy-demanding cellular activity that occurs progressively from the nucleolus to the cytoplasm. In the nucleolus, precursor rRNAs associate with a myriad of trans-acting factors and some ribosomal proteins to form pre-ribosomal particles. These factors include snoRNPs, nucleases, ATPases, GTPases, RNA helicases, and a vast list of proteins with no predicted enzymatic activity. Their coordinate activity orchestrates in a spatiotemporal manner the modification and processing of precursor rRNAs, the rearrangement reactions required for the formation of productive RNA folding intermediates, the ordered assembly of the ribosomal proteins, and the export of pre-ribosomal particles to the cytoplasm; thus, providing speed, directionality and accuracy to the overall process of formation of translation-competent ribosomes. Here, we review a particular class of trans-acting factors known as “placeholders”. Placeholder factors temporarily bind selected ribosomal sites until these have achieved a structural context that is appropriate for exchanging the placeholder with another site-specific binding factor. By this strategy, placeholders sterically prevent premature recruitment of subsequently binding factors, premature formation of structures, avoid possible folding traps, and act as molecular clocks that supervise the correct progression of pre-ribosomal particles into functional ribosomal subunits. We summarize the current understanding of those factors that delay the assembly of distinct ribosomal proteins or subsequently bind key sites in pre-ribosomal particles. We also discuss recurrent examples of RNA-protein and protein-protein mimicry between rRNAs and/or factors, which have clear functional implications for the ribosome biogenesis pathway.